Genetic and Evolutionary Computing Proceedings of the Ninth International Conference on Genetic and Evolutionary Computing, August 26-28, 2015, Yangon, Myanmar - Volume II - Zin, Thi Thi; Lin, Jerry Chun-Wei; Pan, Jeng-Shyang; Tin, Pyke; Yokota, Mitsuhiro (Advances in Intelligent Systems and Computing,, 2016)
This volume of Advances in Intelligent Systems and Computing contains accepted papers presented at ICGEC 2015, the 9th International Conference on Genetic and Evolutionary Computing. The conference this year was technically co-sponsored by Ministry of Science and Technology, Myanmar, University of Computer Studies, Yangon, University of Miyazaki in Japan, Kaohsiung University of Applied Science in Taiwan, Fujian University of Technology in China and VSB-Technical University of Ostrava. ICGEC 2015 is held from 26-28, August, 2015 in Yangon, Myanmar. Yangon, the most multiethnic and cosmopolitan city in Myanmar, is the main gateway to the country. Despite being the commercial capital of Myanmar, Yangon is a city engulfed by its rich history and culture, an integration of ancient traditions and spiritual heritage. The stunning SHWEDAGON Pagoda is the center piece of Yangon city, which itself is famous for the best British colonial era architecture. Of particular interest in many shopsof Bogyoke Aung San Market, and of world renown, are Myanmar's precious stones-rubies, sapphires and jade. At night time, Chinatown comes alive with its pungent aromas and delicious street food. The conference is intended as an international forum for the researchers and professionals in all areas of genetic and evolutionary computing. .